2018
DOI: 10.1177/0885066618773679
|View full text |Cite
|
Sign up to set email alerts
|

Newly Proposed Sepsis-Induced Coagulopathy Precedes International Society on Thrombosis and Haemostasis Overt-Disseminated Intravascular Coagulation and Predicts High Mortality

Abstract: At baseline, 149 (98.7%) of 151 patients with overt DIC according to the ISTH definition were diagnosed as having SIC. Of the 49, 46 (93.9%) patients who developed overt DIC between days 2 and 4 had received a prior diagnosis of SIC. The sensitivity of baseline SIC for the prediction of death was significantly higher than that of overt DIC (86.8% vs 64.5%, P < .001). The sensitivity of SIC on days 2, 4, and 7 was significantly higher than those of overt DIC (96.1%, 92.3%, and 84.4% vs 67.1%, 57.7%, and 50.0%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 30 publications
3
59
3
3
Order By: Relevance
“…As a result, almost all the patients with overt‐DIC had SIC, and SIC had preceded overt‐DIC in every case. The mortality rate for overt‐DIC was significantly higher than that for SIC (32.5% versus 23.1%) . A comparison of the SIC and JAAM DIC criteria was also carried out, and the prevalence of patients with SIC was comparable to that of patients with JAAM DIC.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…As a result, almost all the patients with overt‐DIC had SIC, and SIC had preceded overt‐DIC in every case. The mortality rate for overt‐DIC was significantly higher than that for SIC (32.5% versus 23.1%) . A comparison of the SIC and JAAM DIC criteria was also carried out, and the prevalence of patients with SIC was comparable to that of patients with JAAM DIC.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…The usefulness of the SIC score has been validated . The ISTH DIC SSC members compared SIC and ISTH overt DIC scoring systems in sepsis patients with coagulopathy . It was found that almost all patients with overt DIC also met criteria for SIC, and that SIC preceded overt DIC in every case.…”
Section: Diagnosis Of Sepsis‐associated Dic and Sicmentioning
confidence: 99%
“…[25][26][27][28] The ISTH DIC SSC members compared SIC and ISTH overt DIC scoring systems in sepsis patients with coagulopathy. 25 It was found that almost all patients with overt DIC also met criteria for SIC, and that SIC preceded overt DIC in every case. In another study, SIC criteria appeared to identify a patient group similar to that identified using JAAM DIC criteria.…”
Section: Range Rangementioning
confidence: 99%
“…26 Recently, active members of the ISTH DIC-SSC recently proposed a simpler version for the diagnosis of SIC that is composed of only three items: sepsis-3 definitions (infection with organ dysfunction), platelet count, and the prothrombin time ratio 27 (►Table 1). The usefulness of these SIC diagnostic criteria has been validated, and Iba et al 28 reported that it provides an earlier diagnosis and includes most cases of ISTH overt DIC. An additional analysis of septic patients from Japan evaluated associations between in-hospital mortality and anticoagulant therapy according to the SIC or ISTH overt DIC sets of criteria.…”
Section: Diagnosis Of Disseminated Intravascular Coagulation Diagnostmentioning
confidence: 99%